Animals can assign novel odours to a known category - Hannah F. Wright (Nature Portfolio, 2017)
Abstract The ability to identify a novel stimulus as a member of a known category allows an organism to respond appropriately towards it. Categorisation is thus a fundamental component of cognition and an essential tool for processing and responding to unknown stimuli. Therefore, one might expect to observe it throughout the animal kingdom and across sensory domains. There is much evidence of visual categorisation in non-human animals, but we currently know little about this process in other modalities. In this experiment, we investigated categorisation in the olfactory domain. Dogs were trained to discriminate between 40 odours; the presence or absence of accelerants formed the categorical rule. Those in the experimental group were rewarded for responding to substrates with accelerants (either burnt or un-burnt) and inhibit responses to the same substrates (either burnt or un-burnt) without accelerants (S+ counterbalanced). The pseudocategory control group was trained on the same stimuli without the categorical rule. The experimental group learned the discrimination and animals were able to generalise to novel stimuli from the same category. None of the control animals were able to learn the discrimination within the maximum number of trials. This study provides the first evidence that non-human animals can learn to categorise non-biologically relevant odour information.